Characteristics of the autism spectrum disorder gastrointestinal and related behaviors inventory in children - Holingue, Calliope; Kalb, Luther G.; Musci, Rashelle; Lukens, Colleen; Lee, Li‐Ching; Kaczaniuk, Jamie; Landrum, Michelle; Buie, Timothy; Fallin, M. Daniele (Autism research, 2022)
Gastrointestinal (GI) symptoms are one of the prevalent co‐occurring issues in autism spectrum disorder (ASD), though the range of symptom frequency estimates varies dramatically across studies, which can limit the further research of GI issues in ASD as well as potential treatment strategies. The wide range of prevalence estimates is partly due to the lack of standardized, validated measures of GI symptoms among people with ASD. The goal of this study was to (1) develop a measure, which included non‐verbal and mealtime behaviors, to assess for GI symptoms and (2) evaluate its psychometric characteristics. This was accomplished by drawing on two existing tools, Autism Treatment Network Gastrointestinal Inventory and the Brief Autism Mealtime Behavior Inventory, and deriving new items, to create the “ASD Gastrointestinal and Related Behaviors Inventory” (ASD‐GIRBI). The ASD‐GIRBI was piloted in an online registry of families with a child with ASD. A psychometric analysis was carried out in a sample of 334 children aged 6–17 years with ASD, resulting in a 36‐item tool. The Cronbach's alpha for the overall scale was 0.88. Exploratory factor analysis identified a seven‐factor model (1. Bowel movement pain; 2. Aggressive or disruptive during mealtimes; 3. Particular with foods; 4. Abdominal pain and upset stomach; 5. Refusing food; 6. Constipation and encopresis; 7. Motor or other behaviors). Following validation in an independent sample with clinical evaluation of GI symptoms, this tool will be helpful for both research and clinical purposes. Lay Summary Gastrointestinal (GI) symptoms are common in children with autism spectrum disorder (ASD), yet assessing these symptoms remains challenging. This study developed a parent‐report, 36‐item questionnaire to measure GI symptoms in children with ASD. The tool included questions about food, mealtimes, GI symptoms, bowel habits, and behavior. This questionnaire may help researchers and clinicians assess GI symptoms among children with ASD.